A network pharmacology-based study on the mechanism of astragaloside IV alleviating renal fibrosis through the AKT1/GSK-3β pathway. (28th October 2022) - Yu, Xinwei; Xiao, Qiming; Yu, Xixi; Cheng, Yu; Lin, Hao; Xiang, Zheng
Abstract: Ethnopharmacological revelvance: Astragaloside IV, a glycoside derived from Astragalus membranaceus, has anti-renal fibrosis effects. However, its mechanism of action has not yet been fully elucidated. Aim of the study: The purpose of this study was to investigate the anti-fibrotic effect of AS-IV and to clarify its underlying mechanism. Materials and methods: The network pharmacology method, molecular docking and surface plasmon resonance (SPR) was used to identify potential targets and pathways of AS-IV. A unilateral ischemia-reperfusion injury (UIRI) animal model, as well as TGF-β1-induced rat renal tubular epithelial cells (NRK-52E) and renal fibroblasts (NRK-49F) were used to investigate and validate the anti-fibrotic activity and pharmacological mechanism of AS-IV. Network pharmacology was performed to construct a drug-target-pathway network. The anti-fibrosis effect of AS-IV was determined using hematoxylin-eosin (H&E) and MASSON staining, as well as immunostaining methods. qRT-PCR and western blotting were used to elucidate and validate the mechanism of AS-IV. Results: Network pharmacology revealed that the PI3K/AKT pathway is an important pathway in AS-IV. AS-IV inhibited the expression of α-SMA, collagen I, and fibronectin in NRK-52E, NRK-49F, and UIRI rats, and reduced serum creatinine and blood urea nitrogen levels in UIRI rats. AS-IV inhibited AKT phosphorylation, blocked GSK-3β phosphorylation, and restored GSK-3β activity, which contributed to the degradation of β-catenin, thereby preventing epithelial-mesenchymal transition (EMT). Conclusion: Astragaloside IV alleviated renal fibrosis through the AKT1/GSK-3β pathway. In addition, our findings indicate that the network pharmacology method is a powerful tool for exploring the pharmacological mechanisms of drugs. Graphical abstract: Image 1 Highlights: Astragaloside IV has a good anti-fibrotic effect in vivo and in vitro . Network pharmacology revealed that PI3K/AKT pathway is an important pathway in AS-IV. Astragaloside IV alleviated renal fibrosis by inhibiting the AKT/GSK pathway.